A modern web-based health promotion program for patients in Greece with diabetes 2 and obesity: an interventional study - Maria S. Chrysi; Ioannis Michopoulos; George Dimitriadis; Melpomeni Peppa (BMC, 2023)
Abstract Background Health promotion programs are most beneficial in chronic diseases such as diabetes and morbid obesity, which can be positively affected by changes in attitudes, beliefs, and lifestyle. Objectives This study aimed to develop an internet-based modern Health Promotion model using interactive online applications through continuing education and participation. Methods The goal was to positively impact knowledge, behavior, and quality of life for patients with obesity and/or diabetes. This is a prospective interventional study on patients with obesity or type 2 diabetes. Seventeen two patients who met the inclusion criteria were distributed randomly into two groups (control and intervention) from 2019 to 2021 in Greece. All the participants were given questionaries concerning quality of life anxiety and depression (HADS) attitudes and beliefs, knowledge about their condition and general questions to establish a baseline. A traditional health promotion model was followed for the control group. For participants in the intervention group, a web-based health promotion program was created according to the goals of the research. Participants were instructed to log on 1-2 times a week for 5-15 min, with the understanding that the research team would be monitoring their activities. The website included two knowledge games and personalized educational material based on their needs. Results The sample comprised 72 patients (36 in control and 36 in the intervention groups). The mean age was 47.8 years for the control group and 42.7 years for the intervention group (p = 0.293). Both study groups had a significant increase in knowledge score on diabetes (Control group:3,24, Intervention group 11,88 p < 0,001) and obesity (Control group:4,9, Intervention group 51,63 p < 0,001) along with a positive attitude score towards fighting obesity (Control group: 1,8, Intervention group 13,6 p < 0,001). Still, the overall change was more remarkable for the intervention group, as indicated by the significant interaction effect of the analysis. Anxiety was decreased only in the intervention group (Control group:0,11, Intervention group − 0,17 p < 0,005). Analysis for QOL during follow-up showed that Physical Health and Level of Independence was improved in both study groups but the degree of improvement was more significant in the intervention group (Control group 0,31,Intervention group 0,73 p < 0,001). Psychological Health was improved only in the intervention group, with better scores at 6 and 12 months compared to controls (Control group 0,28,Intervention group 1,42 p < 0,001). Furthermore, Social relationships were improved only in the intervention group (Control group 0,02, Intervention group 0,56 p < 0,001). Conclusions The results of the present study showed that the participants in the intervention group showed significant improvement in knowledge, attitudes, and beliefs after using the internet as a learning tool. The intervention group also showed significantly reduced anxiety and depression arising from chronic illness. All of this resulted in an improved quality of life regarding physical Health, mental Health, and social relationships. Technology and online-based health promotion programs can revolutionize how we approach the prevention and management of chronic and terminal illnesses by improving accessibility, personalizing care, increasing engagement and motivation, improving data analysis, and disease management.